Pengaruh Metode Pembelajaran Assurance Relevance, Interest Assessment and Satisfaction (Arias) Terhadap Hasil Belajar Matematika Siswa Kelas XI Bina Patria 1 Sukoharjo - Happy P.H, Valenta; Afghohani, Afif; Exacta, Aninsa Prima (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to determine whether there is a significant influence between conventional learning methods and Assurance Relevance, Interest, Assessment and Satisfaction (ARIAS) learning in class XI Bina Patria 1 Sukoharjo students. This study uses quantitative research methods of quasi-experimental type with posttet-only control design. With many 33 experimental class samples and 33 control class samples. Research data obtained from the results of teacher and student interviews, documentation of student learning outcomes, the source of this data comes from teachers and students. Hypothesis calculation using t-test. Before carrying out the t-test, a normality test was carried out using the Liliefors test and a homogeneity test with the Barlet test. The results of the hypothesis calculation obtained then is rejected or 4.845> 2.295 then is rejected so it can be concluded that there is an influence of the ARIAS learning method on learning outcomes.